Can Customer Loyalty Mediate Customer Trust in Business Sustainability at Village Credit Institution? - Sarmawa, I Wayan Gde; Sugianingrat, Ida Ayu Putu Widani (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2022)
The main point of this research was to examine and analyze the impact of customer trust on customer loyalty and business sustainability at the Village Credit Institution in Klungkung Regency. The determination of the VCI as the research sample was carried out by unproportionate random sampling. The research respondents were customers in each VCI who were taken by accident (which was met at the time of the research) with a total number of respondents as many as 170 customers. Analysis this research and hypothesis using the SmartPLS 3.3.2 program with three level, the first is testing validity and reliability, the second is testing the accuracy of the research model, and the third is testing hypotheses. This results in this study indicate that customer trust has a positive relationship and significant impactt on customer loyalty and business sustainability. The customer loyalty has a significant positive effect relationship on business sustainability. Customer loyalty acts as a mediator of customer trust on the business sustainability of VCI in Klungkung Regency.